Perancangan sistem supply terintegrasi dengan konsep Just in time (JIT) pada assembly line - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Supply system as an intregated element of production system should be able to provide the production requirement related to the customer demand. Materials, parts or components supplied has to be match as production requirement to accommodate the production process to reach the produc-tion yield In the assembly line, balance of production line and supply activities is an important factor to reach the production target. Cycle supply time which appears by supply activities should be able to match the production rhythm which represents as takt time. According to Just In Time Concept, supply should be able to accommodate the production requirement at the exact part, exact time and exact amount, so supply done at a range of production time cycle without causing over-stock or shortage-stock at the production line stores. The length of supply cycle time is affected by supply activities which follows the supply pattern for each parts needed. Unconformity supply pattern applied is able to raise the over-stock or shortage stock which causes the appearance of line-stop. In this research, time measurement for each supply activities is needed to get the times data as the reference of design of supply system. According to the milk runs method